Penerapan Teknik Menulis Derby Writing Berbasis Teknologi Informasi di Program Khusus Perkuliahan Bahasa Arab (PKPBA) Universitas Islam Negeri Maulana Malik Ibrahim Malang - Rohmatulloh Salis (Tarling : Journal of Language Education, 2020)
This study aims to determine the application of information technology-based Derby Writing technique in the Arabic Language Center (PKPBA) Universitas Islam Negeri Maulana Malik Ibrahim Malang and students' opinions on the use of it. This research is a descriptive qualitative study. Data sources are learning curriculum, learning process, and students. The research instruments are observation and interview. The data analysis technique used is descriptive qualitative data analysis, namely data reduction, data display and conclusion drawing. The results show that: 1) information technology-based Derby Writing technique in the Arabic Language Center (PKPBA) Universitas Islam Negeri Maulana Malik Ibrahim Malang is applied in several stages, namely: (a) opening and making a WhatsApp group, (b) discussing a topic, (c) asking students to write as many sentences as possible about the topic discussed, taking into account the characteristics of the Derby Writing technique, (d) asking students to take pictures of their writing and sent to the WhatsApp group, (e) students present and discuss the obstacles faced when writing such as new vocabulary, etc., (f) selecting some student writing errors randomly from the WhatsApp group, explaining and correcting them, ( g) looking together at the writings in the WhatsApp group and counting the number of vocabularies to determine the winner, and (h) closing. 2) All students feel happy and think that the application of information technology-based Derby Writing technique is very appropriate because it helps them eliminate fears when writing and improve their habits and enjoyment in writing.